2012
DOI: 10.1017/s0268416012000215
|View full text |Cite
|
Sign up to set email alerts
|

Immigration, wealth and the ‘mortality plateau’ in emergent industrial cities of nineteenth-century Massachusetts

Abstract: The mortality transition in Western Europe and the U.S. encompassed a much more complex set of conditions and experiences than earlier thought. Our research addresses the complex set of relationships among growing urban communities, family wealth, immigration and mortality in New England by examining individual-level, socio-demographic mortality correlates during the nineteenth-century mortality plateau and its early twentieth-century decline. In contrast to earlier theories that proposed a more uniform mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Previous research (Leonard, Beemer, and Anderton 2012; Anderton, Beemer, and Leonard 2005) found that estimating wealth effects on general mortality in this population without an effort to control for healthy worker selection effects among more recently arrived immigrant groups can “confound selection effects from recently arriving immigrants with effects of later periods when the same immigrant group was a more stable residential population”, resulting in longitudinally inconsistent and erroneous results (Leonard, Beemer, and Anderton 2012: 447). Since census data do not record actual individual-level time of arrival over most of the study period, we follow our prior research in using a nested interaction of ethnic group and periods of peak immigration as a proxy for a ‘healthy migrant’ effect on adult mortality.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Previous research (Leonard, Beemer, and Anderton 2012; Anderton, Beemer, and Leonard 2005) found that estimating wealth effects on general mortality in this population without an effort to control for healthy worker selection effects among more recently arrived immigrant groups can “confound selection effects from recently arriving immigrants with effects of later periods when the same immigrant group was a more stable residential population”, resulting in longitudinally inconsistent and erroneous results (Leonard, Beemer, and Anderton 2012: 447). Since census data do not record actual individual-level time of arrival over most of the study period, we follow our prior research in using a nested interaction of ethnic group and periods of peak immigration as a proxy for a ‘healthy migrant’ effect on adult mortality.…”
Section: Methodsmentioning
confidence: 94%
“…The second dataset is an urban-based geographic sample of Federal census records, linked to property tax information and death records in the year following the census, allowing us to analyze personal and family characteristics not available from the death records. Gutman (1956) demonstrates the extraordinary completeness of Massachusetts death reporting and previous research (e.g., Leonard, Beemer, and Anderton 2012) demonstrates representation of the impoverished within the tax-linked dataset. We looked at trends in mortality rates for the entire population using the first dataset, and modeled mortality rates for the sampled census population using Poisson rate regression.…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Poisson models are widely used in epidemiology to model rate data that consists of the number of events (in this study, the number of deaths) divided by the exposure time (person-years at risk) during which the events occurred (Preston 2005). Poisson regression models have been employed in a number of studies of mortality in historical populations (Leonard, Beemer, and Anderton 2012;Leonard et al 2015;Molitoris and Dribe 2016). The Poisson model can be expressed by the following formula (Dalgaard 2008: 262): log ρ = β 0 + β 1 x 1 + β 2 x 2 + …β k x k + log T in which log ρ represents the log rate of the event (death); β 0 represents the constant; x 1, x 2 … x k represent the covariates (occupational group, educational level, ethnic/language group, etc.)…”
Section: Data Variables and Analytical Strategymentioning
confidence: 99%